2022
DOI: 10.1371/journal.ppat.1010343
|View full text |Cite
|
Sign up to set email alerts
|

Diltiazem inhibits SARS-CoV-2 cell attachment and internalization and decreases the viral infection in mouse lung

Abstract: The continuous emergence of severe acute respiratory coronavirus 2 (SARS-CoV-2) variants and the increasing number of breakthrough infection cases among vaccinated people support the urgent need for research and development of antiviral drugs. Viral entry is an intriguing target for antiviral drug development. We found that diltiazem, a blocker of the L-type calcium channel Cav1.2 pore-forming subunit (Cav1.2 α1c) and an FDA-approved drug, inhibits the binding and internalization of SARS-CoV-2, and decreases S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 67 publications
1
9
0
Order By: Relevance
“…Our data is relatively equivalent to that of viral burdens of rh-gal9 treated animals of influenza infected animals ( 20 ). Additionally, consistent to other therapeutics tested in K18-hACE2 mice, viral burdens were reduced in groups that exhibited increase survival frequency compared to controls ( 31 34 ).…”
Section: Discussionsupporting
confidence: 80%
“…Our data is relatively equivalent to that of viral burdens of rh-gal9 treated animals of influenza infected animals ( 20 ). Additionally, consistent to other therapeutics tested in K18-hACE2 mice, viral burdens were reduced in groups that exhibited increase survival frequency compared to controls ( 31 34 ).…”
Section: Discussionsupporting
confidence: 80%
“…The results indicated that these target genes of eugenol highly enriched in the biological processes, pathways of human diseases and SARS-CoV-2 pathway (e.g. Ca2 + signaling) [ 128 ], including complement and coagulation cascades, calcium signaling pathway, viral infection, and cancers. The SymMap symptoms manifested that eugenol was significantly associated to headache and pain, and some neurological symptoms, upper respiratory tract symptoms, and gastrointestinal symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Several cellular proteins have been reported to affect the entry of viruses. For example, the L-type calcium channel Ca v 1.2 pore-forming subunit is an entry factor for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and influenza A virus ( 9 , 10 ); GRP78 is an entry factor for Japanese encephalitis virus ( 11 ), and Coxsackievirus ( 12 ); and TIM-1 is an entry factor for Chikungunya virus and hepatitis C virus ( 13 , 14 ). Identifying novel conserved entry factors and exploring the underlying mechanisms are essential to develop broad-spectrum antiviral drugs that block early infection.…”
Section: Introductionmentioning
confidence: 99%